Food sovereignty and agricultural trade policy commitments: how much leeway do West African nations have? - (:unkn) unknown (My University, 2011)
The 2008 food crisis has challenged the political legitimacy and economic efficiency of the liberalization of international agricultural trade. An alternative vision defended by the food sovereignty movement is that longterm food security cannot rely on dependency on food imports, but must be built on the development of domestic production with enough barrier protection to shelter it from world price fluctuations and unfair trading. The purpose of this paper is to look into whether the West African nations can achieve food sovereignty given their various trade commitments and other external constraints. The particularity of our approach is to combine a historical economic analysis with a political approach to food sovereignty and trade commitments. Our results suggest that external brakes on the development of food sovereignty policies are marginal, as the countries still have unused room for manoeuvre to protect their smallholder agriculture under the terms of draft World Trade Organization agreements and Economic Partnership Agreements and under the international financial institutions' recommendations. Rather the international environment seems to be instrumented by West African states that do not manage to secure a national political consensus to drive structural reforms deemed vital and further the food security of the urban populations over the marginalized rural populations. Recently, the regional integration process has made headway with a common agricultural support and protection policy project that could herald an internal political balance more conducive to food-producing agriculture.
Keywords: African Research